Studi Keragaman Jenis Hewan Invertebrata di Kawasan Curug Goong Kecamatan Padarincang Kabupaten Serang Banten - Haerani, Yeni; Hermawan, Hermawan; Haniyah, Putri Nur; Ramdani, Resa Mohamad (Jurnal Kajian Pendidikan IPA, 2023)
Research conducted in the Curug Goong area is a study with exploratory descriptive methods, research conducted also obtained a variety of phyla including annelid, mollusca and arthropod phyla from these phyla also get various types of animals including earthworms and leeches of annelid phyla, poison snails, river snails, gold snails including mollusca phylum and the last phylum arthropods are dragonflies, black ants, red ants, grasshoppers, butterflies, millipedes, scorpions, spiders, shrimp and river crabs. The total calculation of the diversity index or (H') is 2,507, the value is also included in the “Medium” category. The medium category is included in the condition of evenly distributed. Keywords: Diversity, Invertebrates, Curug Goong